Allicin shows antifungal efficacy against Cryptococcus neoformans by blocking the fungal cell membrane - Li, Zhun; Li, Zhengtu; Yang, Jun; Lu, Chun; Li, Yongming; Luo, Yinzhu; Cong, Feng; Shi, Rongmei; Wang, Zhen; Chen, Huaying; Li, Xinxia; Yang, Jinglu; et al. (Frontiers in Microbiology, 2022)
Objective: Allicin, which is generated by the catalytic reaction between alliin and alliinase extracted from garlic, has been shown to have a wide range of antimicrobial activities, but its anti-cryptococcus efficacy and mechanism are not quite clear. Methods：Firstly, the minimum inhibitory concentration (MIC) of allicin against 46 strains of Cryptococcus neoformans(C. neoformans) and the effect of allicin combined with clinical anti-cryptococcal drugs (FICI) were determined. Then, the effect of allicin on the growth of Cryptococcus in vitro at different time points was detected by time-killing curve and real-time microscope imaging. Finally, we verified the efficacy of allicin in vivo. Further, transcriptomics was used to explore the possible sites and pathways of allicin acting on Cryptococcus, and finally verified by transmission electron microscopy (TEM) and Confocal laser scanning microscopy (CLSM). Results: Here, the Conversion rate of allicin in the reaction product reached 97.5%. The MIC of allicin against C. neoformans H99 was 2 μg/ml, which is comparable to fluconazole (FLU, 1 μg/ml), but somewhat different from amphotericin B (AmB, 0.125 μg/ml). Furthermore, allicin exhibited effctive antifungal activity against 46 clinical isolates of C. neoformans, and the MICs ranged from 1 to 8 μg/ml, even for AmB-insensitive strains. Interestingly, allicin also exerted additive or synergistic effects when combined with AmB and FLU. Time-killing curves and real-time imaging of live H99 showed that 4 MIC of allicin had fungicide activity. Additionally, allicin (4 and 8 mg/kg) exerted a dose-dependent therapeutic effect on H99-infected mice by significantly reducing the pulmonary index and Cryptococcus load and improving lung damage. Even the efficacy of 8 mg/kg was comparable to FLU (20 mg/kg). Transcriptomics revealed that allicin may act on the cell membrane of H99. Subsequently, TEM observations showed that allicin clearly breached the cell membrane and organelles of H99. CLSM results further confirmed that allicin disrupted the permeability of the cell membranes of H99 in a dose-dependent manner. Conclusion: Allicin exhibits strong anti- C. neoformans activity in vitro and vivo, mainly by destroying the permeability and related functions of Cryptococcus  cell membranes.